Analysis of clinico-demographic risk factors for postoperative pulmonary complications following gastrointestinal surgery - Sinouvassan, Vijay; Dayalane, Hemalatha; Balagurunathan, Subalakshmi; Sahoo, Ashok Kumar; Kanth, Vishnu; Thirthar Palanivelu, Elamurugan (International Surgery Journal, 2019)
Background: Postoperative pulmonary complications (PPC) are one of the commonest complications following gastrointestinal surgery. They lead to increased mortality, increased length of intensive care unit (ICU) stay, and higher cost of treatment. Identifying the risk factors of PPC helps in predicting its occurrence and to develop preventive measures. The objectives of the present study were to study the clinical and demographic risk factors for PPC following gastrointestinal surgery. Methods: The study was designed as an observational descriptive analytic study. All the patients ≥18 years of age undergoing gastrointestinal surgery were included. The patients with preoperative lung pathology requiring ICU care or ventilatory support and patients with lung metastasis were excluded. The demographic and clinical parameters at admission were recorded. The details of pulmonary complications like the time of occurrence after surgery and the mode of treatment for pulmonary complications were noted. The risk association was assessed for statistical significance. Results: A total of 100 patients were underwent various gastrointestinal surgeries during the study period. The incidence of PPC was 34% in our study. Age, education status, smoking, and presence of comorbidities were found to be positively associated with an increased incidence of PPCs. The serum albumin of less than 3.5gm and the haemoglobin of less than 8 gm were also associated with an increased incidence of PPC. Pleural effusion was the commonest PPC seen in 15 (44.1%) patients followed by pneumonia in 9 (26.5%). Conclusions: Age, smoking, education status, serum albumin, haemoglobin, emergency surgery, elective postoperative ventilation, nasogastric intubation and blood loss in the intraoperative period were found to associated with increased risk of PPCs.